An Inferential Study on the Profitability Determinants of the Cement Industry in Bangladesh - Rezina, Sonia; Ashraf, Aysha; Khan, Md. Atiqullah (Asian Finance & Banking Review, 2020)
This paper examines the impacts of firm-specific and macroeconomic factors in determining the profitability of the cement industry in Bangladesh. This study took stock exchange listed all cement companies of Bangladesh as samples and covered the period of 2000–2018. Return on Assets (ROA) was chosen as the dependent variable and firm size, expense to revenue ratio, leverage, age, inflation rate, GDP growth rate, and real interest rate were chosen as independent variables where the first four are firm-specific and the other three are macroeconomic factors. This study considered ROA as the profitability measurement of the firms. The study found that leverage, GDP growth rate, and real interest rate have significant impacts on the profitability. Firm size, age, GDP growth rate, and real interest rate have a positive impact whereas expenses to revenue ratio, leverage, and inflation have a negative impact on the profitability of the firms under the cement industry.